2019
DOI: 10.32929/2446-8355.2019v28n3p343-353
|View full text |Cite
|
Sign up to set email alerts
|

Períodos de secagem na qualidade fisiológica de sementes de cacau

Abstract: As sementes deAs sementes de cacau recém-colhidas apresentam elevado teor de água o que impede o armazenamento, devido à rápida perda da viabilidade e vigor. Diante do exposto, objetivou-se no presente trabalho avaliar a influência de diferentes períodos de secagem na qualidade fisiológica de sementes de cacau. O delineamento experimental utilizado foi o inteiramente casualizado com os tratamentos constituídos de quatro períodos de secagem das sementes (0, 24, 48 e 72 horas) com quatro repetições. As sementes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…There can be a rapid loss of viability between perceiving the opportunity for germination and dehydration. Pereira et al (2019), in their experiment with cocoa seeds, found that germination is maximum (100%) with water content of 69.79%, but when the humidity decreases to 21.1%, germination is only 40%.…”
Section: Resultsmentioning
confidence: 98%
“…There can be a rapid loss of viability between perceiving the opportunity for germination and dehydration. Pereira et al (2019), in their experiment with cocoa seeds, found that germination is maximum (100%) with water content of 69.79%, but when the humidity decreases to 21.1%, germination is only 40%.…”
Section: Resultsmentioning
confidence: 98%